Embodied and enactive approaches to cognition - Gallagher, Shaun, 1948- (Cambridge elements. Elements in the philosophy of mind,, 2023)
This Element discusses contemporary theories of embodied cognition, including what has been termed the '4Es' (embodied, embedded, extended and enactive cognition). It examines diverse approaches to questions about the nature of the mind, the mind's relation to the brain, perceptual experience, mental representation, sense making, the role of the environment, and social cognition, and it considers the strengths and weaknesses of the theories in question. It contrasts embodied and enactive views with classic cognitivism, and discusses major criticisms and their possible resolutions. This element also provides a strong focus on enactive theory and the prospects for integrating enactive approaches with other embodied and extended theories, mediated through recent developments in predictive processing and the free energy principle. It concludes with a brief discussion of the practical applications of embodied cognition. This title is also available as Open Access on Cambridge Core.